"Another Way to Talk About Feeling Bad". Creative Interactive Bibliotherapy – A Complement to Treatment for Women with Mental Illness After Childbirth. Issue 1 (2nd January 2022) - Pettersson, Cecilia
ABSTRACT: The purpose of this study is to investigate whether and in what respects creative interactive bibliotherapy can affect the mental and social well-being of women with postpartum mental illness. Four women with mental illness after childbirth read and discussed fiction in a reading circle for ten weeks, under the guidance of a licensed psychologist. The participants were observed during the reading circle and interviewed individually when the reading circle had ended. ). The result of the study shows that the women's social, mental, and intellectual well-being was positively affected. The participants felt less alone. Their thoughts and emotions were stimulated. They were strengthened in their identity, prioritized their own needs and became more active in their everyday lives. Given the results, creative interactive bibliotherapy seems to be a form of therapy that merits further research regarding the group of women with postpartum mental illness.